Psychometric evaluation of the Persian version of the stressor scale for emergency nurses - Reza Ghanei Gheshlagh; Nishtman Pour Mohammadi; Fazel Dehvan; Hamid Sharif-Nia (Nursing Practice Today)
Background & Aim: Emergency nurses face unique stressors that increase their occupational stress. Most existing tools measure general stress and overlook emergency-specific factors. This study aimed to assess the psychometric properties of the Persian version of the Stressor Scale for Emergency Nurses. Methods & Materials: This is a cross-sectional study that used the forward-backward method to translate the tool from English to Persian. Face and content validity were assessed by five emergency nurses and five nursing faculty members, respectively. Construct, known-group, and convergent validity were tested in 198 emergency nurses from Saqqez and Sanandaj hospitals (2024). Test-retest reliability was evaluated in 21 nurses over two weeks. Internal consistency was measured using Cronbach’s alpha and McDonald’s omega. Data were analyzed using Jamovi 2.4.14. Results: Face and content validity were satisfactory. Exploratory factor analysis identified four factors—conflicts, life and death situations, patients' families' actions and reactions, and technical/formal supports, which explained 60.64% of total variance. Convergent validity showed a correlation of 0.554 between job stress scores based on the Stressor Scale for Emergency Nurses and the Brief Nursing Stress Scale. Known group validity revealed that occupational stress scores were higher in women than men, and there was a significant negative correlation between occupational stress and work experience in the emergency department. Cronbach's alpha and McDonald's omega coefficients were 0.953 and 0.954, respectively; the intraclass correlation coefficient was 0.943. Conclusion: The Persian version of the stressor scale shows strong psychometric properties and is reliable for assessing occupational stress in emergency nurses.